Towards Intelligent Manufacturing Systems for Industrial Revolution 4.0 : An Overview - Syahrul Nizam, Junaini; Mohd Saleh, Abbas; Zakaria, Amir; Sarina, Mail; Farah, Zeehan; Muhaimin Haziq, Mihat (Kalahari Journals, 2022)
Throughout the previous decade, the fourth industrial revolution has created many chances to enhance manufacturing and production processes. These innovations aim to bridge the divide between physical and digital technology in order to create a more intelligent and efficient manufacturing system. To completely grasp the relationship between intelligent manufacturing and IR4.0, first, we begin with reviewing eight advantages of intelligent manufacturing in relation to IR 4.0. Second, while deploying an intelligent manufacturing system inspired by AI has several benefits, it also introduces several complications. Finally, we see Cyber Physical Systems (CPS) as an innovative option for researching and developing intelligent manufacturing processes.